(untitled) (Proceedings of International Educators Conference, 2024)
History is one of the important subjects that help students to understand their historical heritage, culture and society. In the modern educational process, interactive methods play an important role in increasing the effectiveness of history teaching, increasing students’ interest and ensuring their active participation. In this article, we will talk about interactive methods used in teaching history and their advantages.